Effect of Cold Plasma on Quality Retention of Fresh-Cut Produce - Hadi Bagheri; Sepideh Abbaszadeh (Journal of Food Quality)
In recent years, the consumption of the fresh-cut products has been increased due to the consumers’ lifestyle and awareness. However, maintaining the quality and nutritional value of these products during storage is being difficult in comparison to whole fruits and vegetables. In actual, the procedures used in the fresh-cut industry may intensify the deterioration caused by physical damage by minimal processing. Commonly, the quality degradation, discolouration, loss of moisture, loss of firmness, microbial load increase, and loss of nutrients and flavor occur in the fresh-cut product after minimal processing. To maintain the quality and increase the shelf-life of the fresh-cut product, it is necessary to use various techniques, including physical, chemical, and nondestructive processes. In this review, first, an introduction to minimal processing and its effect on fresh-cut product quality was expressed, and then, the methods used to maintain fresh-cut product quality after minimal processing were reviewed. Finally, the effect of cold plasma on the qualitative characteristics in some fresh-cut products was investigated. The review showed that cold plasma treatments can significantly inhibit microorganisms and extend the shelf-life of fresh-cut products. In addition, no or minimal impacts were observed on physicochemical and organoleptic quality attributes of the treated fresh-cut products. Therefore, the use of cold plasma is promising for the fresh-cut industry.